155 Children Evaluated by Department of Forensic Medicine Dokuz Eylul University Medical Faculty - Ergönen, Akça Toprak; Sönmez, Ersel; Özdemir, Mehmet Hakan; Demiroğlu, Zehra; Salaçin, Serpil (The Bulletin of Legal Medicine, 2006)
It is widely known that childhood injuries differ with regard to the causes and results from adulthood injuries and most of them are preventable. This study aims to constitute a database of injuries among children who were assessed medico-legally in our department. We investigated 155 cases (36% girls, 64% boys) aged 0-18 (mean age 10.88) who were admitted to our department between 1998 and 2005. Our most significant finding was that most of the cases were injured by traffic accident, especially pedestrians. There were multiple traumas in 51% of the cases. 61% of the cases stayed in the hospital and 42% of cases had surgical treatment. We also observed that intentional injuries were more common than other injuries among children over 12 years old and this finding was statistically significant (y2=6.321, p= 0.012). Our study showed that, improving the education in schools and family is a necessity to prevent injuries because of traffic accidents in childhood. In addition, we are in the opinion that more studies are needed for preventing childhood injuries due to violence in our country. Key words: Childhood injuries, medicolegal evaluation, traffic accident, violence.